PENGARUH PERPUTARAN PIUTANG DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN KIMIA - Purnamasari, Diah Ayu; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of account receivable turnover and firm size to the profitability, to find out the efficiency in managing account receivable and to increase the profitability of the company. 10 companies have been selected as samples with the observation period from 2011 to 2013 (3 years), so the total data that has been selected as samples are 30 firm year. The multiple regressions equation is used in this research in order to find out the independent variables which have influence to the dependent variable. The analysis has been carried out by using the SPSS 16 software. Based on the result of multiple regressions analysis with the significance level of 5%, thus this research shows that i.e.: (1).H1 which is the influence of firm size to the profitability with its significance level is 0.047 can be accepted since the value of t count is 1.909 which shows the positive direction; (2). H2 which is the influence of account receivable turnover to the profitability with its significance level is 0.044 can be accepted since the value of t count is 2.114 which shows the positive direction.Keywords: Profitability, Firm Size, and Account Receivable Turnover.